Basic and behavioral characteristics of tourists: A case study of Montenegrin coast - Bigović Miloš (University Educons, Faculty of Sports and Tourism, Novi Sad, 2013)
The purpose of this paper is to provide an overview of the characteristics of tourists who visit the Montenegrin coast. In order to achieve this goal, this paper emphasizes two general categories that can be used to examine the tourists' characteristics. The first category refers to the basic characteristics of tourists, while the second refers to their behavioral characteristics. The study was conducted on a quota sample of 703 respondents who visited six Montenegrin coastal destinations in August 2012. The obtained results show numerous implications for the destination, and the most prominent ones refer to the following: (1) 36.13% of the respondents knew the Montenegrin coast as a tourist destination so well that they had no need to be informed about the destination before the departure; (2) 82.93% of the respondents were not at the tourist destination for the first time; (3) 36.84% of the respondents decided to visit the Montenegrin coast more than three months prior to departure; and (4) 59.89% of the respondents emphasized that their expenses related to their stay at the destination were going to be larger than planned before the departure.